2017
DOI: 10.1051/0004-6361/201630267
|View full text |Cite
|
Sign up to set email alerts
|

Deep into the Water Fountains

Abstract: Context. The formation of large-scale (hundreds to few thousands of AU) bipolar structures in the circumstellar envelopes (CSEs) of post-Asymptotic Giant Branch (post-AGB) stars is poorly understood. The shape of these structures, traced by emission from fast molecular outflows, suggests that the dynamics at the innermost regions of these CSEs does not depend only on the energy of the radiation field of the central star. Aims. Multi-frequency observations towards a group of post-AGB sources known as Water Foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…From our SPLASH-ATCA data, we obtain a flux density of 0.9 mJy at 2.1 GHz, although the image is heavily contaminated by sidelobes from other sources in the field. A more reliable value of 0.6 mJy at 2 GHz was obtained by Pérez-Sánchez et al (2017). These authors also showed that the spectral index of the radio continuum emission is consistent with free-free emission from an ionized jet.…”
Section: Radio Continuum Emission: Photoionized Nebulae or Windsmentioning
confidence: 71%
See 1 more Smart Citation
“…From our SPLASH-ATCA data, we obtain a flux density of 0.9 mJy at 2.1 GHz, although the image is heavily contaminated by sidelobes from other sources in the field. A more reliable value of 0.6 mJy at 2 GHz was obtained by Pérez-Sánchez et al (2017). These authors also showed that the spectral index of the radio continuum emission is consistent with free-free emission from an ionized jet.…”
Section: Radio Continuum Emission: Photoionized Nebulae or Windsmentioning
confidence: 71%
“…and continuum emission (within 5 ), even if the maser might be associated with an evolved star, but a literature search showed that the continuum emission traces an extragalactic object. We also detect IRAS 18043-2116, a WF post-AGB star (Walsh et al 2009), whose radio continuum emission has been studied by Pérez-Sánchez et al (2017). The remaining sources with a positive match, are reported in Table 2.…”
Section: Ohpne Candidates In Splash-atcamentioning
confidence: 80%
“…According to the model proposed by Elitzur et al (1989), when the shocked material cools down, H 2 and H 2 O molecules form in gas that is maintained at T k =400 K. As mentioned above, for this temperature the luminosity ratio L p (22 GHz)/L p (321 GHz) is expected to be 5. Comparing the intensities of the 22 GHz masers (see Deacon et al 2007;Walsh et al 2009;Yung et al 2011;Pérez-Sánchez et al 2017) and the 321 GHz masers of IRAS 18043−2116 and IRAS 18286−0959, we find a luminosity ratio ≈1. This implies a kinetic temperature T k >1000 K for the gas (Neufeld & Melnick 1990;Yates et al 1997).…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, this source is also a water fountain source with the water maser emission distributed over a velocity spread of nearly 400 km s −1 (Walsh et al 2009). Pérez-Sánchez et al (2017) also detected the radio continuum emission toward this source, which could arise from a thermal radio jet. In the GLIMIPSE three-color image, this star is very bright at 8 µm.…”
Section: G353810+1452mentioning
confidence: 79%